RF circuit design - Li, Richard Chi-Hsi, 1938- (Wiley, 2012)
"The author divides the book in three portions: (1) summarizes the schemes and technologies in RF circuit design, (2) describes the basic parameters of an RF system and the fundamentals of RF system design, and (3) an introduction of the individual RF circuit block design. The book begins explaining the different methodologies between RF and digital circuit design. It then moves into voltage and power transportation, impedance matching in narrow-band case and wide-band case, gain of a raw device, measurement, and grounding. Also covered are Equipotentiality and current coupling on ground surface, as well as layout and packaging, manufacturability of product design, and Radio Frequency Integrated Circuit (RFIC). Part 2 of the book includes content on the main parameters and system analysis in RF circuit design, the fundamentals of Differential Pair and Common Mode Rejection Ratio (CMRR), Balun, and System-on-a-chip (SOC). Finally, Part 3 covers Low Noise Amplifier (LNA), Mixers, Tunable Filters, Voltage-Controlled Oscillator (VCO), and Power Amplifiers (PA). All of the chapters have end-of-chapter exercises, as well as appendix"-- Vydavatelská anotace
Keywords: radioelektronické obvody; radioelectronic circuits; monografie; monographs